Erythema nodosum in childhood: evaluation of ten patients - Cengiz, A Bülent; Kara, Ateş; Kanra, Güler; Seçmeer, Gülten; Ceyhan, Mehmet (The Turkish Journal of Pediatrics, 2006)
Erythema nodosum (EN), which is a rare skin manifestation among children, is precipitated by a range of infectious and non-infectious diseases. The purpose of this study was to evaluate the epidemiology, etiology, clinical manifestations and course of EN among children. A total of 10 patients diagnosed with EN between January 2000 and March 2004 at Hacettepe University Ihsan Doğramaci Children's Hospital, Pediatric Infectious Diseases Outpatient Clinic, were studied retrospectively. The study population consisted of five girls and five boys, with a mean age of 8.8 +/- 3.3 years (range, 4-14 years). In five of the 10 children (50%), the etiology of EN was established: three had streptococcal infection and two were diagnosed as primary tuberculosis; the etiology of EN could not be determined in 50% of the cases. The duration of the recovery of lesions varied from 4 to 12 days (mean, 8.2 +/- 2.6 days). Our data confirm the predominance of streptococcal infections among the etiologic factors while also considering tuberculosis as a causative factor among children with EN in Turkey.